63‐1: Invited Paper: High Performance Top Emission Quantum‐Dot Light‐Emitting Devices. Issue 1 (28th June 2021) - Hou, Wenjun; Xu, Wei; Yan, Yiran; Liu, Wenyong; Wu, Longjia; Lu, Zizhe; Zhou, Likuan; Yang, Yixing; Yan, Xiaolin
Abstract : Quantum dot light‐emitting diode (QLED) is expected to be a promising technology for the next generation display due to the unique advantages of quantum dots (QDs) materials. Great progress of QLEDs has been implemented by material synthetic optimizations and device fabrication improvements to meet commercial applications, including efficiency and lifetime. Meanwhile, high performance QLEDs were developed by the well‐controlling of the cavity length, which will accelerate the mass production of QLEDs display.